Pengaruh Penggunaan Media Interaktif Kahoot Terhadap Hasil Belajar Siswa Mata Pelajaran Fikih - Annisa' Jamilatussholicha; Santi Lisnawati; Nurman Hakim (At-Tadris: Journal of Islamic Education, 2025)
This study aims to determine the effect of using Kahoot interactive media on student learning outcomes in fiqh subjects in class XI at MAN 1 Bogor Regency. This research uses quasi-experimental quantitative research methods. The population used in this study were all students in grade XI at MAN 1 Bogor Regency Cirimekar Campus by taking a sample of 74 students using purposive sampling technique. Data collection techniques through tests in the form of pretests and posttests. The data analysis technique used is the Mann-Whitney test. Based on the results of the Mann-Whitney test calculation of the control and experimental class posttest data, the value of significance (2-tailed) is obtained as follows significance (2-tailed) was found to be 0.002 <0.005. So, from this statement it can be concluded that there is a significant and real difference in student learning outcomes in the control and experimental classes. significant and real differences in student learning outcomes in fiqh subjects by looking at the posttest results of the control and experimental classes. posttest results from the control class and the experimental class.